2011
DOI: 10.1002/jcb.23245
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of inflammation by N‐arachidonoylglycine

Abstract: N-arachidonoylglycine (NAgly) is an endogenous signaling lipid that is a member of the eicosanoid super family and is related to anandamide. It shows anti-inflammatory activity in vivo in the mouse peritonitis model where it reduces migration of inflammatory leukocytes following injection of pro-inflammatory agents into the peritoneal cavity. Using cell culture models, including GPR18 transfected HEK-293 cells, evidence is presented that the orphan receptor GPR18 is involved in this action. Increases in free a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 21 publications
2
54
0
Order By: Relevance
“…Furthermore, it was recently reported that N-arachidonoyl-glycine also possessed anti-inflammatory actions [51]. Meanwhile, N-palmitoyl-glycine seemed to show a proinflammatory effect, suggesting the structural importance of N-acyl-LPC activity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was recently reported that N-arachidonoyl-glycine also possessed anti-inflammatory actions [51]. Meanwhile, N-palmitoyl-glycine seemed to show a proinflammatory effect, suggesting the structural importance of N-acyl-LPC activity.…”
Section: Discussionmentioning
confidence: 99%
“…Again, CBD was more active than THC in stimulating phopholipid hydrolysis. By way of comparison, the anti inflammatory actions of cannabinoid analogs such as NAgly 24 and ajulemic acid ( Fig. 2) 25 have been attributed to their ability to promote the release of free arachidonic acid.…”
Section: Arachidonic Acid Releasementioning
confidence: 99%
“…Using a screening process, these researchers discovered that N-arachidonylglycine (NAGly) stimulated Ca(2+) influx and inihibited forskolin-induced cAMP accumulation in GPR18-transfected cells to a greater extent that control cells, and concluded that NAGly is a endogenous ligand for GPR18. Of particular interest for the central nervous system, there is some evidence that GPR18 may have antinociceptive effects through direct effects on nociceptive fibres [29], though more evidence points towards the modulation of inflammation [30] and pain via effects on immune cells including macrophages [31] and microglia [21] and on vasodilatation.…”
Section: Receptor Targets For O-1602mentioning
confidence: 99%